2019
DOI: 10.1093/pm/pnz200
|View full text |Cite
|
Sign up to set email alerts
|

Men, Chronic Pain, and Prescription Pain Medication Use: The Role of Gender Role Beliefs in a Longitudinal Moderated Mediation Model

Abstract: Objective Although past research has established that men with chronic pain are more likely to misuse prescription pain medications in a myriad of ways compared with women, little is known about men’s medication use in the context of their gender role beliefs. The aim of the present study was to examine the role of men’s domestic gender role beliefs on their use of prescription pain medication for chronic pain. Methods Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
(107 reference statements)
1
2
0
2
Order By: Relevance
“…Regarding validity, scale scores were positively associated with pain severity, pain catastrophizing, anxiety, and depression (Ryan & McGuire, 2016). In a MIDUS sample with chronic pain, items yielded a Cronbach's α of .91 (Daheim et al, 2019). Scale items designated excellent internal consistency (Cronbach's α = .91) in the present study.…”
Section: Methodssupporting
confidence: 47%
“…Regarding validity, scale scores were positively associated with pain severity, pain catastrophizing, anxiety, and depression (Ryan & McGuire, 2016). In a MIDUS sample with chronic pain, items yielded a Cronbach's α of .91 (Daheim et al, 2019). Scale items designated excellent internal consistency (Cronbach's α = .91) in the present study.…”
Section: Methodssupporting
confidence: 47%
“…Importantly, these beliefs have been shown to impact on how pain is expressed and responded to, [156][157][158] including with pain medication use. 48 Gender beliefs also affect how men and women view the pain of others, and how observers respond to those in pain. 3,69,75,150,158,164 For example, Hirsh et al 73 found that when viewing virtual patients, observers rated women as having more pain and worse at coping.…”
Section: Individual Gender Context Of Painmentioning
confidence: 99%
“…yaptıkları araştırmada erkeklerin kadınlara göre ağrıyla ilgili daha az kelime, daha az açıklayıcı bir dil kullandıklarını saptamışlardır [23]. Erkekler arasındaki grup içi farklılıkları inceleyen bazı araştırmalarda da yüksek düzeyde geleneksel maskulen kimliklere sahip erkeklerin ağrıları için yardım arama ve ağrıyla ilgili belirtileri açıklama olasılıklarının daha düşük olduğu gösterilmektedir [6]. Bir kadının varlığının erkeklerin ağrıya dayanmasını güçlendirdiği de bir diğer tespittir [22].…”
Section: Erkeklerde Ağrıunclassified
“…Keywords: Pain, Chronic Pain, Gender Identity, Culture Ağrı ve toplumsal cinsiyet rollerindeki ilişki, bu değişkenlerin çok çeşitli kronik durumlarda sahip olabileceği role ilişkin bir iç görü de sağlamaktadır [5]. Örneğin, daha yüksek düzeyde geleneksel maskulen kimliklere sahip erkeklerin ağrıları için yardım arama ve ağrı ile ilgili semptomları açıklama olasılıklarının daha düşük olduğu saptanmıştır [6]. Bu doğrultuda derlemenin amacı, genel olarak ağrıda toplumsal cinsiyet rolü ve kültürün etkisi incelenmiştir.…”
Section: Introductionunclassified